National Mainstreaming Workshop on Climate Risk Management in Agricultural Extension (CRMAE) for Ethiopia - Belay, Berhanu; Ambaw, Gebermedihin; Amha, Yosef; Dinku, Tufa; Hansen, James; Demissie, Teferi; Solomon, Dawit (Accelerating Impacts of CGIAR Climate Research for Africa, 2024)
Climate change education is pivotal in national adaptation and mitigation efforts, creating awareness and advancing the technology needed to build climate resilience. It is, therefore, essential that Ethiopian education programs at all levels incorporate knowledge about climate. The country’s strategy to achieve comprehensive climate literacy includes curriculum intervention, capacity-building trainings and infrastructural development. With the understanding of the sensitivity of agriculture to climate change, the Ethiopian Agricultural Technical and Vocational Education and Training (ATVET), which primarily produces a middle-level workforce that supports the extension system, acknowledges the importance of integrating Climate Risks Management in Agricultural Extension (CRMAE) into ATVET curricula. To support this effort, AICCRA, partnering with the International Research Institute for Climate and Society (IRI), developed a training manual on CRMAE and offered training to ATVET teaching staff. A national CRMAE workshop was also organized to support mainstreaming climate risk management into the ATVET occupational standard that serves all agriculture programs. The Teaching, Training and Learning Materials (TTLM) in the crop production II program was opted for since it was in the pipeline, which would ease the implementation of the program ATVET curriculum. The workshop employed various approaches, including presentations, group discussion and cross-fertilization of ideas. Lessons learned from the process include the presence of strong willingness and collaboration among partners to address climate change challenges in the existing and proposed climate education. The program development regarding occupational standards, curriculum, and TTLM is also a learning experience that can be translated into any training program, including short-term courses. As a recommendation, conference participants underscored the need to extend the same activity to other disciplines as soon as possible.